Experimental Approach to Chemical Evolution - Brij Bhushan Tewari; Davendradat Doodnauth (New Ideas Concerning Science and Technology Vol. 11, 2021)
The origin of life processes began with formation of important biomonomers from simpler molecules present in the prebiotic environment and their subsequent condensation to biopolymers. Effects on pH base adsorption of nucleic acid bases (thymine and uracil) at two different concentrations 1 x 10-4 M and 1 x 10-5 M on copper, cobalt and silver ferrocyanides were studied over a pH range (10 – 10.0) at a temperature of 30±1°C. The progress of adsorption were followed spectrophotometrically by measuring the UV absorbance of nucleic acid base solutions at their corresponding ?max. Maximum adsorptions were found at neutral pH for both thymine and uracil. Effects of concentrations on adsorption of thymine and uracil on copper, cobalt and silver ferrocyanides were studied in a concentration range 1 x 10-4 M - 1 x 10-5 M at a neutral pH 7.0 ± 0.1 and at temperature of 30±1°C. The interaction followed the Langmuir type of adsorption in general in the concentration range of 10-4 to 10-5 M of thymine and uracil solution. The uptake of nucleic bases on metal ferrocyanides followed the order of CuFc > AgFc > CoFc for the adsorption of thymine and CuFc > CoFc > AgFc for the adsorption of uracil. Effects of the presence of salts on the adsorption of thymine and uracil on metal ferrocyanides also had been studied. The insoluble metal ferrocyanides’ interaction with biomolecules must have either formed metal complexes or could have enhanced the formation of biopolymers in fluctuating environment. Adsorption of glycine and ß- alanine on nickel, cobalt and cadmium ferrocyanides and adsorption of dl - aspartic acid, dl – leucine, dl – lysine and dl – serine on halosite, hectorite, illite, kaolinite, nantronite and montmorillonite clay minerals is also reported.